Activation of JAK/STAT3 restores NK‐cell function and improves immune defense after brain ischemia. Issue 5 (8th January 2018) - Jin, Wei‐Na; Ducruet, Andrew F.; Liu, Qiang; Shi, Samuel Xiang‐Yu; Waters, Michael; Zou, Ming; Sheth, Kevin N.; Gonzales, Rayna; Shi, Fu‐Dong
Abstract : Stroke‐induced immune suppression predisposes the host to infections and can contribute to high morbidity and mortality in stroke patients. Because ischemic stroke has a profound effect on the systemic immune response, which may explain the increased susceptibility of stroke patients to infection, an urgent need persists for a better understanding of mechanisms associated with immune suppression; new and effective treatments for stroke can then be identified. NK cells play a key role in early host defense against pathogens by killing infected cells and/ or producing cytokines such as IFN‐γ. Because the phenotype and function of peripheral NK cells have been widely investigated in ischemic stroke, nCounter Inflammation Gene Array Analysis was used to build immune‐related gene profiles of NK cells to comprehensively analyze the molecular signature of NK cells after ischemic brain injury. We observed distinct gene expression profiles reflecting different splenic NK‐cell phenotypes and functional properties across the time course of transient middle cerebral artery occlusion (MCAO). Based on gene expression and pathway‐network analysis, lower expression levels of signal transducer and activator of transcription‐3 (STAT3) were observed in animals with MCAO compared with sham control animals. Genetic activation of STAT3 through the introduction of STAT3 clustered regularly interspaced short palindromic repeats (CRISPR) plasmid prevented the loss of NK‐cell‐derived IFN‐γ production after MCAO, together with reduced bacterial burden and mortality. Our data suggest that brain ischemia impairs NK‐cell‐mediated immune defense in the periphery, at least in part through the JAK‐STAT3 pathway, which can be readdressed by modulating STAT3 activation status.—Jin, W.‐N., Ducruet, A. F., Liu, Q., Shi, S. X.‐Y., Waters, M., Zou, M., Sheth, K. N, Gonzales, R., Shi, F.‐D. Activation of JAK/ STAT3 restores NK‐cell function and improves immune defense after brain ischemia. FASEB J. 32, 2757–2767 (2018). www.fasebj.org